Roles of Different Signaling Pathways in Cryptococcus neoformans Virulence - Fawad Mahmood; Jun-Ming Chen; Ammar Mutahar Al-Huthaifi; Abdullah Ali Al-Alawi; Tong-Bao Liu (Journal of Fungi)
Cryptococcus neoformans is a widespread fungal pathogen that can infect the human central nervous system (CNS) and cause fungal meningitis, leading to hundreds of thousands of deaths worldwide each year. Previous studies have demonstrated that many signal transduction pathways are crucial for the morphological development and virulence of C. neoformans. In this review, data from over 116 research articles have been compiled to show that many signaling pathways control various characteristics of C. neoformans, individually or in association with other pathways, and to establish strong links among them to better understand C. neoformans pathogenesis. Every characteristic of C. neoformans is closely linked to these signaling pathways, making this a rich area for further research. It is essential to thoroughly explore these pathways to address questions that remain and apply a molecular mechanistic approach to link them. Targeting these pathways is crucial for understanding the exact mechanism of infection pathogenesis and will facilitate the development of antifungal drugs as well as the diagnosis and prevention of cryptococcosis.